Overtourism in Coastal Territories in the Perspective of Cruise Tourism: The Role of Human Capita - Brito, Mónica (2021)
This chapter aims to highlight the role of human capital linked to tourism in its multiple dimensions—host community, tourism professionals, and visitors—in resolving or reducing the negative impacts of excess tourist demand in certain coastal territories, where cruise tourism is responsible for the annual arrival of thousands of visitors. Taking Lisbon as a case study, the author analyzes the relationship between quantity between residents and visitors arriving in the territories on cruise ships, the geographical position of the main tourist attractions in order to assess the degree of concentration of visitors, and evidence relating to reciprocal behaviour and attitudes between visitors and visitors, based on the Doxey Irritability Index.